Comparing Prone Positioning Use in COVID-19 Versus Historic Acute Respiratory Distress Syndrome. (13th May 2022) - Hochberg, Chad H.; Psoter, Kevin J.; Sahetya, Sarina K.; Nolley, Eric P.; Hossen, Shakir; Checkley, William; Kerlin, Meeta P.; Eakin, Michelle N.; Hager, David N.
Abstract : IMPORTANCE: Use of prone positioning in patients with acute respiratory distress syndrome (ARDS) from COVID-19 may be greater than in patients treated for ARDS before the pandemic. However, the magnitude of this increase, sources of practice variation, and the extent to which use adheres to guidelines is unknown. OBJECTIVES: To compare prone positioning practices in patients with COVID-19 ARDS versus ARDS treated before the pandemic. DESIGN, SETTING, AND PARTICIPANTS: We conducted a multicenter retrospective cohort study of mechanically ventilated patients with early moderate-to-severe ARDS from COVID-19 (2020–2021) or ARDS from non-COVID-19 pneumonia (2018–2019) across 19 ICUs at five hospitals in Maryland. MAIN OUTCOMES AND MEASURES: The primary outcome was initiation of prolonged prone positioning (≥ 16 hr) within 48 hours of meeting oxygenation criteria. Comparisons were made between cohorts and within subgroups including academic versus community hospitals, and medical versus nonmedical ICUs. Other outcomes of interest included time to proning initiation, duration of prone sessions and temporal trends in proning frequency. RESULTS: Proning was initiated within 48 hours in 227 of 389 patients (58.4%) with COVID-19 and 11 of 123 patients (8.9%) with historic ARDS (49.4% absolute increase [95% CI for % increase, 41.7–57.1%]). Comparing COVID-19 to historic ARDS, increases in proning were similar in academic and community settings but were larger in medical versus nonmedical ICUs. Proning was initiated earlier in COVID-19 versus historic ARDS (median hours (hr) from oxygenation criteria, 12.9 vs 30.6; p = 0.002) and proning sessions were longer (median hr, 43.0 vs 28.0; p = 0.01). Proning frequency increased rapidly at the beginning of the pandemic and was sustained. CONCLUSIONS AND RELEVANCE: We observed greater overall use of prone positioning, along with shorter time to initiation and longer proning sessions in ARDS from COVID-19 versus historic ARDS. This rapid practice change can serve as a model for implementing evidence-based practices in critical care.